Slope and formality characteristics and its effect on the density of natural vegetation in the Pradust mountain range using GIS and RS - Abdul Hussein, Hussein Kazem; Hussein, Zeina Khaled (Journal of Humanities & Social Sciences, 2017)
The research aims to study the characteristics of the formal regressions on the natural vegetation in agricultural intensity Pradost Mountains, located in the province of Arbil in northern Iraq as part of Iraq's Kurdistan region series, with a series area (288.36 km2). Through research have been identified as the physical characteristics (geological, climatic, topographic, natural plant, cultivated land) as well as to identify the spatial distribution of each of these characteristics. Through research have been identified regression formal qualities that form of rectal type of first Alvesm forms slopes and regular Section II of the forms slopes reached area (122.99 km2) Any percentage (42.65%) of the total area of the chain and the form of the convex of the first section forms slopes reached area (89.44 km 2) any percentage (31.02%) of the total area of the chain.A search has been classified vegetation, depending on the value of plant coverage coefficient (NDVI) to three type as preoccupied density of the medium type more than half of the chain space with an area of (206.86 km2) Any percentage (71.74%) of the total overall space for the series, showed results the density of the extreme type increasing proportion within the regular regression from what is in irregular gradient, which demonstrates that the regular gradient advantage of being equal to the currencies of weathering and erosion reverse irregular gradient which has not seen stability yet because of the different angles of slope, making it difficult invested before the occupants in the field of agriculture and the use of agricultural machinery.
Keywords: morphological gradient; density; vegetation cover; Bradost Mountains